Tephritis azari, a New Fruit Fly (Diptera: Tephritidae) from Iran and Azerbaijan, with a Key to the Tephritis maccus Species Group - Namin, Saeed Mohamadzade; Korneyev, Severyn V. (Zootaxa, 2012)
Tephritis azari sp. nov., from mountains of the northwestern part of Iran and Azerbaijan is described and illustrated. It is closely related to T. maccus Hering and T. urelliosomima Korneyev & Dirlbek based on characters of the wing pattern and aculeus. In addition a key to the species of the T. maccus species group has been provided.